Managing retained placenta in first-parity doe and administering vitamin A, D, and E as supportive treatment - Dhea Salsabila; Viski Fitri Hendrawan (Universitas Airlangga, 2024)
This study aims to report the treatment of retained placenta in a doe by administration of intrauterine antibiotics, accompanied by intramuscular injection of antibiotics, anti-inflammatory, and injection of vitamins A, D, and E as supportive treatment. The Saanen doe was brown, approximately two years old with a BCS of 3/5 and kidding for the first time on January 11, 2023. The following day, it was reported that the doe's placenta had not been expelled until 24 hours after kidding. Physically the doe was weak, unable to stand, and reddish-brown discharge was seen came out of the vulva. Based on these conditions the doe was diagnosed as having retained placenta with a fausta prognosis. The doe was treated with a bolus of antibiotics contained 250 mg sulphadiazine and 50 mg trimethoprim which was diluted with 5 mL of 0.9% NaCl for uterine lavage. Systemic treatment consisted of intramuscular injection of ceftiofur at 1.1 mg/kg bw, flunixin meglumine at 1.1 mg/kg bw, as well as a combination of 300,000 IU of vitamin A palmitate, 100,000 IU of vitamin D3, and 50 mg of vitamin E acetate as supportive treatment. The treatment was successful, the doe was able to stand and eat when examined the next day after treatment. The doe returned to estrus 42 days after treatment. It could be concluded that treatment of retained placenta in a doe with intrauterine broad-spectrum antibiotics, beta-lactamase antibiotics and intramuscular anti-inflammatory, with vitamins A, D and E as supportive therapy was effective and the doe returned to estrus 42 days after treatment.